Intranasal phage treatment overcomes the limitations posed by antibody-mediated neutralization in bacteriophage therapy for Pseudomonas aeruginosa lung infections - Dhammika Leshan Wannigama; Cameron Hurst; Peter N Monk; Paul G. Higgins; Tanittha Chatsuwan; Anthony Kicic; Parichart Hongsing; Shuichi Abe; Stephen M Stick (Journal of Global Antimicrobial Resistance)
Background: Our recent work discovered that intranasal inhalation of phage (KKP10) and Ca-EDTA substantially re-sensitized multidrug-resistant P. aeruginosa to ceftazidime/avibactam. Notably, the route of phage administration was reported to influence the development of antibody-mediated neutralization of phage and thereby reducing its therapeutic efficiency. Therefore, we evaluated the effectiveness of KPP10 regimens utilizing systemic intraperitoneal (IP) and localized intranasal routes to treat chronic P. aeruginosa lung infection. Methods: The effectiveness of KPP10 regimens utilizing systemic intraperitoneal (IP) and localized intranasal routes to treat chronic P. aeruginosa lung infection, were access using mouse lung infection model togeter with ELISA to measured the production of neutralizing antibodies (IgM, IgG, and IgA). RESULTS: In this study, pre-treatment of mice with KPP10 intraperitoneally induced the systemic distribution of KPP10 to different internal organs, whereas intranasal KKP10 pre-treatment achieved significant KPP10 localization exclusively in alveolar space and elsewhere in lungs. Interestingly, intraperitoneal KPP10 administration regimens in chronic lung infection resulted in decreased survival with significant IgG, IgM, and IgA production. Meanwhile, after giving KPP10 regimens intranasally, anti-phage antibody production was undetectable and survival improved significantly. Conclusions: These results demonstrated that administering KPP10 directly to the lungs via the intranasal route could ensure a higher concentration of KPP10 at the infection site, expediting its bactericidal effects for increased pathogen elimination, while overcoming antibody-mediated phage neutralization and improving clinical outcomes in chronic pulmonary P. aeruginosa infections.